An ultrasonic assisted dissolution of feather keratin / Nur Afiqah Azmi - Nur Afiqah , Azmi (2019)
Feather keratin is a biomass generated in excess from various livestock industries. Upon proper processing, it holds potential as a green source for degradable biopolymer that could possibly replace current fossil fuel-based materials. Several processing methods have been developed, but the report on the use of ultrasonication was not found. In this study, our work focuses on (i) optimising and comparing the dissolution process of turkey feather keratin through sonication and conventional processes, and (ii) generating a biodegradable polymeric material, as a value-added product, from the dissolved keratin that could be used in packaging and other applications. Sonication of feather keratin in pure ionic liquid (ILs) and mixtures containing ILs and different co-solvents were conducted under different applied acoustic power levels. It was found that ultrasonic irradiation significantly improved the rate of dissolution of feather keratin as compared to the conventional method, by approximately 90 % improvement in dissolution time. The amount of ILs required was also successfully reduced by introducing a suitable co-solvent. The keratin was then regenerated, and the characteristics was analysed using a combination of analytical techniques which are ATR-FTIR, PXRD, TGA, and DSC. From these techniques, it was observed that the protein backbone is still intact, and no major chemical changes of the polypeptide chains occur through ultrasonic method. This material holds the potential to be reused in various applications.